Evaluation of the effects of 980 and 810-nm high-level diode lasers in treating dentin hypersensitivity: A double-blinded randomized clinical trial - Narges Naghsh; Marzie Kachuie; Mahdieh Bijari; Reza Birang (Wolters Kluwer Medknow Publications, 2022)
Background: Dentin hypersensitivity is a prevalent problem, manifested as a short sharp pain. Researchers have used different lasers to treat this condition. The present study aimed to evaluate the effect of 980 and 810-nm high-level diode lasers on dentin hypersensitivity to determine proper laser parameters for clinical applications. Materials and Methods: In this double-blinded randomized clinical trial, seven patients with 60 teeth affected by dentin hypersensitivity were selected for the present double-blind, randomized clinical trial. The patients' teeth were randomly matched and assigned to three groups: Group 1: 980-nm diode laser; Group 2: 810-nm diode laser; and Group 3: Control, which received only the guiding beam. The laser parameters were 1-W power, continuous wave mode, a distance of 1 mm, no contact, a 45° irradiation angle, and a 30-s exposure time using to-and-fro movements. The treatment consisted of two sessions with a 1-week interval. Pain severity was determined with the visual analog scale (VAS) at all the study intervals using a dry ice spray. The data were analyzed with SPSS version 20 using one-way ANOVA, repeated measures ANOVA, and least significant difference tests. Significance level was set at α = 0.05. Results: The changes in VAS were significant only in the first stage (P = 0.046). The mean VAS scores decreased over time in the 810-nm and 980 laser groups. A comparison of VAS changes relative to the baseline revealed significant changes in VAS scores at all the time intervals with both lasers. The two 810 and 980-nm laser groups did not exhibit any significant differences for 2 months postoperatively (P = 0.098). Conclusion: The application of 810 and 980-nm diode lasers at 1-W power and an exposure time of 30 s was effective in decreasing pain in patients with dentin hypersensitivity, with no significant difference between these two lasers.